1978
DOI: 10.1038/bjc.1978.201
|View full text |Cite
|
Sign up to set email alerts
|

Lodgement and extravasation of tumour cells in blood-borne metastasis: an electron microscope study

Abstract: These results indicate that thromboplastic activity of tumour cells might be important in forming microthrombi in the lodgement phase and might be one of the factors facilitating blood-borne metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Furthermore, it has been stressed that the most important factors influencing the ability to form fibrin with clumping of tumour cells would be fibrinolytic activity of tumour cells themselves rather than that of blood itself (Warren, 1973;Kinjo, 1978). While both t-PA and u-PA cleave the same single peptide bond in plasminogen to convert it into plasmin, t-PA is distinguished by its high affinity for fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been stressed that the most important factors influencing the ability to form fibrin with clumping of tumour cells would be fibrinolytic activity of tumour cells themselves rather than that of blood itself (Warren, 1973;Kinjo, 1978). While both t-PA and u-PA cleave the same single peptide bond in plasminogen to convert it into plasmin, t-PA is distinguished by its high affinity for fibrin.…”
Section: Discussionmentioning
confidence: 99%
“…The non-receptor tyrosine kinase Src, the first identified oncogene (see Guarino, 2010;Irby and Yeatman, 2000 for review), induces the formation of invadopodia (see Murphy and Courtneidge, 2011 for review), which are dynamic and actin-rich protrusions detected in many highly invasive cancer cell lines derived from solid tumors such as breast, melanoma and fibrosarcoma (Linder et al, 2011;Murphy and Courtneidge, 2011). Invadopodia are enriched in matrix-metalloproteases (MMPs) and are necessary at many stages of the metastatic process such as breaking through the basement membrane (Kinjo, 1978) and extravasating through blood vessels (Leong et al, 2014;see Lohmer et al, 2014;Paz et al, 2014 for review). Invadopodia are regulated downstream of many RhoGTPases for review), formed downstream of Src activation (Chen et al, 1985) and induced in response to a variety of external stimuli (see Linder et al, 2011;Murphy and Courtneidge, 2011 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports (Peterson, 1968;Tanaka et al, 1977;Clark, 1979;Donati et al, 1978) have suggested that the coagulation-fibrinolysis system plays different roles in the various stages of metastasis. Some workers (Jones et al, 1971;Warren & Vales, 1972;Chew & Wallace, 1976;Kinjo, 1978) have demonstrated the association of fibrin with tumour-cell emboli in distant organs. Fibrin formation may aid in tumour arrest and adherence to blood vessel endothelium.…”
mentioning
confidence: 99%